The authoritarian moment : how the left weaponized America's institutions against dissent - Shapiro, Ben (HarperCollins Publishers, 2021)
We all come to moments when we face pivotal decisions, but many feel that they have no guidance for how to make good choices. In 'The Authoritarian Moment', Ben Shapiro lays out the seven most important decisions we'll ever make, and provides a framework for how to make those decisions with virtue and wisdom.